2010
DOI: 10.4055/cios.2010.2.3.140
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Prognostic Analysis of Adjacent Segments after Spinal Fusion

Abstract: BackgroundTo examine the survival function and prognostic factors of the adjacent segments based on a second operation after thoracolumbar spinal fusion.MethodsThis retrospective study reviewed 3,188 patients (3,193 cases) who underwent a thoracolumbar spinal fusion at the author's hospital. Survival analysis was performed on the event of a second operation due to adjacent segment degeneration. The prognostic factors, such as the cause of the disease, surgical procedure, age, gender and number of fusion segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 26 publications
0
36
3
Order By: Relevance
“…Although some previous clinical studies have reported that older patients are at a significantly higher risk of developing ASD after lumbar fusion surgery, some clinicians still believe that there is no correlation between age and ASD [25][26][27][28][29]. Our present results suggest that old age significantly elevates the hazard ratio for this condition.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Although some previous clinical studies have reported that older patients are at a significantly higher risk of developing ASD after lumbar fusion surgery, some clinicians still believe that there is no correlation between age and ASD [25][26][27][28][29]. Our present results suggest that old age significantly elevates the hazard ratio for this condition.…”
Section: Discussioncontrasting
confidence: 64%
“…Because we only evaluated fusion surgery cases at 1-2 spinal levels (L4-5 and L4-S1) as the index surgery, the proportion of our patients who developed CASD was most likely less than expected. Nonetheless, an earlier study by Ahn et al [26] reported 97 and 94 % disease-free survival rates in their patient cohort at 5 and 10 years, respectively. We believe that the inclusion of additional cases and a longer observation period would probably elevate our 10 year disease-free survival rate; that is, the percentage of patients who were followed over the 10 year observation period was probably too small to accurately assess the 10 year disease-free survival rate.…”
Section: Discussionmentioning
confidence: 92%
“…Facet joint degeneration can contribute to recurrent back pain after TDR [10,[33][34][35]. The patient in case 1 had an anterior spinal fusion at L5-S1, which can accelerate facet joint degeneration, as well as unnatural motions in the L4-L5 Activ-L TDR [36][37][38]. In case 2, the patient received a two-level TDR which can lead to hypermobility and accelerates facet joint degeneration [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…7,9 Furthermore, lumbar fusion surgery for degenerative disc disease (DDD) and discogenic LBP also referred to as discogenic fusion, has been associated with variable clinical outcomes, particularly when compared with fusion for more definable instability, such as spondylolisthesis. [10][11][12][13][14][15][16][17][18] Some RCTs have reported significant improvement in Oswestry Disability Index (ODI) after discogenic fusion, but upon pooling data in a meta-analysis, Bydon et al recently reported no significant difference compared with nonoperative therapy. 18 DDD and discogenic LBP are estimated to now be the most common indications for lumbar fusion in the United States, as rates of discogenic fusion have increased approximately 220% since 1990.…”
mentioning
confidence: 96%